The Effect of Product Quality, Price, Distribution and Promotion on Demand for Xiaomi Smartphone in Surabaya - Reza Akbar Mauliza; I Made Suparta (eCo-Buss, 2024)
Smartphone competition is getting tighter, companies are starting to create various labels or brands of their own products, one of the brands that has succeeded in attracting consumer attention is Xiaomi. This study aims to determine the effect of product quality, price, distribution and promotion on the demand for Xiaomi phones in Surabaya. This research is quantitative research using Accidental Sampling technique and uses primary data processed from the results of distributing questionnaires to 105 respondents who own Xiaomi as a research sample. The analysis techniques used include t-test, F-test, R2 and multiple linear regression analysis with the SPSS 26 program. The results of this study indicate that partially the product quality variable has a positive and significant effect, partially the price variable has a negative and significant effect, partially the distribution has a positive and significant effect, and partially the promotion has a positive and insignificant effect. Simultaneously product quality, price, distribution and promotion have a significant effect on demand.